The Influence of Word Of Mouth, Facebook Ads and Personal Selling On the Purchase Decision of Points of Sales (Pos) Packages at Senna - Achmad Noorman Setiawan; Moh. Agung Surianto (Indonesian Vocational Research Journal, 2022)
This study aims to analyze the effect of word of mouth, facebook ads and personal selling on purchasing decisions at PT Senna Kreasi Nusa. This study uses a quantitative approach. The population in this study were consumers of PT. Senna Kreasi Nusa. The sampling technique used in this study is a non-probability sampling technique which produces a sample of 75 consumers. The data collection technique used is a questionnaire. The data was obtained by using multiple linear regression analysis, first the instrument test and classical assumption test were performed. The results showed that the variables word of mouth, facebook ads and personal selling had a positive and significant effect on the purchasing decisions of PT. Senna Kreasi Nusa.